Kajian atas Pemenuhan Hak Jaminan Sosial Melalui BPJS sebagai Perwujudan Negara Kesejahteraan (Walfare State) - Ishviati Joenaini Koenti (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Study of Sistem Jaminan Sosial Nasional (SJSN)–National Social Insurance System is new, given embodiment SJSN beginning with the creation of the newly passed through Badan Penyelenggara Jaminan Sosial (BPJS)-Implementing Bodies Social Insurance on November 25, 2011. Social insurance is the mandate of the CONSTITUTION Article 28 H UUD NRI 1945, paragraph (3) States that everyone is entitled to social security that allows the development of her intact as human dignity. In addition, article 34 paragraph 2 state, that the State develop a social insurance system for the whole people and empowering nation with the dignity of humanity. Social insurance is also a Human Right that is present on the International Covenant on economic, social and Cultural. ( ICCESC) though its fulfillment as well as interdependent with civil and Political Rights. The Covenant recognizes the need for the fulfilment of these rights are gradually, some of the obligations that a burden countries are urgent.Social insurance is currently not yet covered all citizens of Indonesia, itsconvinience is very limited. It’s still limited to formal sector workers (private, civil servant, and TNI/Polri), the poor population are covered only partly which were classified under the poverty line and no design minimum standards for many forms of insurance and social assistance, in addition to the management of National Social insurance Systems (SJSN) derect by many institutions that not integrated. To more understand the scheme-a scheme there is good legal basis, scope of benefits, beneficiaries, as well as their funding systems, needs to be done the mapping the current social protection systems. Since November 12, 2011 there is already a legal umbrella for managing social insurance through Act No. 24 of the Badan Penyelenggara Jaminan Sosial (BPJS) but in terms of coverage of social insurance there are still some areas that have not been done by existing schemes.